Ultrasound-Triggered Effects of the Microbubbles Coupled to GDNF Plasmid-Loaded PEGylated Liposomes in a Rat Model of Parkinson's Disease - Yue, Peijian; Miao, Wang; Gao, Lin; Zhao, Xinyu; Teng, Junfang (Frontiers in Neuroscience, 2018)
Background: The purpose of this study was to investigate ultrasound-triggered effects of PEGylated liposomes-coupled microbubbles mediated gene transfer of glial cell line-derived neurotrophic factor (GDNF) plasmid (PLs-GDNF-MBs) on behavioral deficits and neuron loss in a rat model of Parkinson’s disease (PD). Methods: The unloaded PLs-MBs were characterized for particle size, concentration and zeta potential. PD rat model was established by a unilateral 6-hydroxydopamine (6-OHDA) lesion. Rotational, climbing pole and suspension tests were used to evaluate behavioral deficits. The immunohistochemical staining of tyrosine hydroxylase (TH) and dopamine transporter (DAT) was used to assess the neuron loss. The expression levels of GDNF and nuclear receptor-related factor 1 (Nurr1) were determined by western blot and qRT-PCR analysis. Results: The particle size of PLs-MBs was gradually increased, while the concentration and absolute zeta potential were gradually decreased in a time-dependent manner after injection. 6-OHDA elevated amphetamine-induced rotations and decreased the TH and DAT immunoreactivity compared to sham group. However, these effects were blocked by the PLs-GDNF-MBs. In addition, the mRNA and protein expression levels of GDNF and Nurr1 were increased after PLs-GDNF-MBs treatment. Conclusions: The delivery of PLs-GDNF-MBs into the brains using MRI-guided focused ultrasound alleviates the behavioral deficits and neuron loss in the rat model of PD.